Legal Regulatory Readiness in Accommodating Non-Fungible Token as Objects of Fiduciary Collateral - Aristias, Adinda; Taupiqqurrahman (Dinasti Research, 2025)
This research aims to analyze the readiness of Indonesia’s legal framework to accommodate Non-Fungible Tokens (NFTs) as fiduciary collateral objects and to identify the potential obstacles in their execution process. NFTs are digital assets based on blockchain technology that possess unique characteristics and economic value, theoretically fulfilling the criteria of intangible objects under Law Number 42 of 1999 concerning Fiduciary Collateral. However, the current legal instruments in Indonesia have not yet explicitly recognized NFTs as eligible fiduciary objects. This study employs a normative juridical method with both statutory and case approaches, supported by secondary data derived from an interview with the Direktorat Jenderal Administrasi Hukum Umum (Ditjen AHU) to enrich the legal analysis. The findings indicate that Indonesia’s regulatory readiness regarding NFTs as fiduciary collateral remains conceptual rather than operational. The absence of a registration mechanism and valuation system for digital assets creates significant legal uncertainty for both creditors and debtors. Furthermore, the execution of NFTs presents additional challenges, including the dependence on private keys, the incompatibility of automatic smart contract transfers with the due process of law principle, and the speculative volatility of NFT market values. Therefore, the study suggests the need for new legal norms and an authorized digital asset valuation institution to ensure that NFTs can be effectively and lawfully integrated into Indonesia’s fiduciary security system. Non-Fungible Token, Fiduciary Collateral, Collateral Execution, Intangible Assets